(untitled) (Research, Society and Development, 2025)
Chronic Kidney Disease (CKD) is a progressive and irreversible condition frequently observed in felines, characterized by the gradual loss of renal function and associated metabolic and systemic alterations. This study aims to report a case of CKD in a three-year-old, male, mixed-breed cat (SRD) treated at a veterinary clinic in Cacoal-RO, Brazil. The animal presented a history of sporadic vomiting, polyuria, polydipsia, and hyporexia. Laboratory tests revealed elevated urea and creatinine levels, associated with low urine specific gravity, while ultrasonography showed increased cortical echogenicity and partial loss of corticomedullary differentiation. Based on the clinical and laboratory findings, the patient was classified as stage II CKD, according to IRIS (2023) guidelines. The treatment included a specific renal diet, subcutaneous fluid therapy, an angiotensin-converting enzyme inhibitor (ACEI), and potassium supplementation, resulting in clinical improvement and stabilization of biochemical parameters after 30 days of follow-up. This report highlights the importance of early diagnosis and individualized therapeutic management, demonstrating that, although incurable, CKD can be effectively controlled through updated protocols and continuous monitoring.